Comparative assessment of phytoremediation potential of four Ficus spp. under Semi-arid environmental conditions: Phytoremediation potential of Ficus spp - Yasin, Ghulam; Bin Yousaf, Muhammad Talha; uz Zaman, Qamar; Farooq Azhar, Muhammad; Muhammad, Asif Javed; Al Obaid, Sami; Javed Ansari, Mohammad; Ur Rahman, Shafeeq (Cellular and Molecular Biology, 2024)
Heavy metals have been recognized as a prominent hazard in today's world, causing pollution in the air environment. Woody tree species can play a significant role in the extraction and remediation of metal pollutants from the air, therefore promoting the air quality index. This study investigated the potential of four species of the Ficus genus (F. benjamina, F. microcarpa, F. religiosa, and F. virens) to remediate varying levels of heavy metal contamination in industrial, residential, and highway areas of Faisalabad City, Pakistan. For this purpose, six heavy metals (cadmium, chromium, copper, lead, zinc, and manganese) were assessed in young leaves (YL) as well as old leaves (OL) of subjected tree species at selected study sites. Eight fully expanded leaves were selected from each tree species: two from each cardinal direction from the shoot of the current year (young leaves, YL), as well as from the shoot of the previous year (old leaves, OL). The results showed that the same genus has different capabilities to accumulate different heavy metals, and the overall trend was in the following order: F. virens > F. religiosa > F. benjamina > F. microcarpa at all study sites. The heavy metal contents in both YL and OL of selected tree species decreased in the order of Manganese (Mn)> Zinc (Zn)> Copper (Cu) > Chromium (Cr) > Lead (Pb) > Cadmium (Cd) at all study sites. The metal accumulation index (MAI) values ranged between 2.14-5.42 for F. benjamina, 2.09-3.89 for F. microcarpa, 3.61-7.01 for F. religiosa and 4.77-6.48 for F. virens across all study sites. Among the studied tree species, it has been determined that F. virens and F. religiosa are well-suited for urban areas with significant heavy metal contamination and can be strategically planted in barrier areas to effectively combat atmospheric pollution.